1999
DOI: 10.1021/bi991610i
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Mechanism for Half-the-Sites Reactivity in an Enzyme, Thymidylate Synthase, Involves a Relay of Changes between Subunits

Abstract: Thymidylate synthase (TS), a half-the-sites reactive enzyme, catalyzes the final step in the de novo biosynthesis of deoxythymidine monophosphate, dTMP, required for DNA replication. The cocrystal structure of TS from Pneumocystis carinii (PcTS), a new drug target for an important pathogen, with its substrate, deoxyuridine monophosphate (dUMP), and a cofactor mimic, CB3717, was determined. The structure, solved at 2.6 A resolution, shows an asymmetric dimer with two molecules of the substrate dUMP bound yet on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 28 publications
7
88
0
Order By: Relevance
“…During PDDF titration, Trp fluorescence at 332 nm was quenched related to the binding of PDDF, but an emission at 379 nm appeared, suggesting a fluorescence resonance energy transfer (FRET) between the WT TS and PDDF. A similar red shift in maximum emission during binding was reported in the literature for TS from Lactobacillus casei (Sharma & Kisliuk, 1975) and Pneumocystis carinii (Anderson, O'Neil, DeLano & Stroud, 1999). Trp fluorescence experiments indicate that the K48Q mutant has a lower affinity for both antifolates, consistent with the ITC data.…”
Section: Folate Binding For the K48q Mutantsupporting
confidence: 88%
See 1 more Smart Citation
“…During PDDF titration, Trp fluorescence at 332 nm was quenched related to the binding of PDDF, but an emission at 379 nm appeared, suggesting a fluorescence resonance energy transfer (FRET) between the WT TS and PDDF. A similar red shift in maximum emission during binding was reported in the literature for TS from Lactobacillus casei (Sharma & Kisliuk, 1975) and Pneumocystis carinii (Anderson, O'Neil, DeLano & Stroud, 1999). Trp fluorescence experiments indicate that the K48Q mutant has a lower affinity for both antifolates, consistent with the ITC data.…”
Section: Folate Binding For the K48q Mutantsupporting
confidence: 88%
“…Trp fluorescence was used to observe the antifolate binding regarding to the Trp residues at the active site (W80 and W83) (Anderson, O'Neil, DeLano & Stroud, 1999;Felder, Dunlap, Dix & Spencer, 2002;Lovelace, Gibson & Lebioda, 2007;Sharma & Kisliuk, 1975). Samples were prepared by dialysis as described above for ITC.…”
Section: Tryptophan Fluorescencementioning
confidence: 99%
“…The utility of negative cooperativity in the nitrogenase mechanism is not obvious, just as, to our knowledge, there are no cases of substantiated advantages of this phenomenon in other enzymes (32)(33)(34)37). That said, it can be imagined that when the events on one side are communicated to the other side, this may facilitate conformational changes that contribute to unidirectional electron flow from the Fe protein to the FeMo-co, or that favor the dissociation of the discharged Fe protein.…”
Section: Discussionmentioning
confidence: 97%
“…Although limited, crystallographic studies of such oligomeric systems have indicated that binding of the first ligand may distort the shape of the unliganded subunit, thereby rendering the binding of the second ligand more unfavorable 18,39 . Nevertheless, other crystallographic studies have failed to reveal any obvious structural effect on the unfilled subunit in the intermediate complex that could account for the observed negative cooperativity 18,40,41 , raising the possibility that other mechanisms may act to increase the energy of the second binding step.…”
Section: Discussionmentioning
confidence: 99%